Social Movements and Institutions - Coelho, Maria Francisca Pinheiro (Revista de Estudos e Pesquisas sobre as Américas, 2017)
Â  Abstract This study approaches the relationship between social movements and institutions in Brazil concerning three different stages of the process of re-democratization: the political transition; the National Constituent Assembly; and the new Constitutional Order. The general question is: what is the interface, reciprocity or conflict, between social movements and institutions in this context of social change? The paper examines the different roles of social movements and institutions in each specific period: in the pre-democratization moment, the movement for direct elections for president, Diretas-Já, is analyzed; in the National Constituent Assembly, the movement in defense for free public education is examined;Â  in the new constitutional order, the pro-reform political movement is studied.Â  The work focuses on the scope of the studies on social movements and democracy.Â  It belongs to the field of the studies about the representativeness and legitimacy of the demands of social movements in the context of democracy and its challenges. Key words: social movement, institution, reciprocity, conflict, democracy. Â  Social Movements and InstitutionsÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Resumen El estudio aborda la relación entre los movimientos sociales e instituciones en Brasil en tres etapas diferentes del proceso de redemocratización en las últimas décadas: la transición política; la Asamblea Nacional Constituyente; y el nuevo orden constitucional. La pregunta general es: ¿cuál es la relación, la reciprocidad o el conflito, entre los movimientos sociales y las instituciones en este contexto de cambio social? El artículo examina los diferentes roles de los movimientos sociales e instituciones en cada período específico: en el momento de la transición política analiza el movimiento de las elecciones directas para presidente, las Diretas-Já; en la Asamblea Nacional Constituyente aborda el movimiento en defensa de la educación pública y gratuita; en el nuevo orden constitucional se estudia el movimiento pro-reforma política. El trabajo se centra en el ámbito de los estudios sobre los movimientos sociales y la democracia. Pertenece al campo de la investigación sobre la representatividad y la legitimidad de las demandas de los movimientos sociales en el contexto de la democracia y sus desafíos. Palabras clave: movimientos sociales, instituciones, reciprocidad, conflicto, democracia. Â  Social Movements and InstitutionsÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Resumo O estudo aborda a relação entre movimentos sociais e instituições no Brasil em três diferentes fases do processo de democratização nas últimas décadas: a transição política; a Assembleia Nacional Constituinte; e a nova ordem Constitucional. A questão geral é a seguinte: qual a interface, reciprocidade ou conflito entre os movimentos sociais e instituições neste contexto de mudança social? O artigo examina os diferentes papéis dos movimentos sociais e instituições em cada período específico: no momento da transição política analisa o movimento de eleições diretas para presidente, o Diretas-Já; na Assembleia Nacional Constituinte aborda o movimento em defesa da educação pública e gratuita; na nova ordem constitucional focaliza o movimento pela reforma política. O trabalho centra-se no campo dos estudos sobre movimentos sociais e democracia. Pertence ao campo de pesquisa sobre a representatividade e legitimidade das demandas dos movimentos sociais no contexto da democracia e seus desafios. Palavras-chave: movimentos sociais, instituições, reciprocidade, conflito, democracia.